การเปรียบเทียบการก่อสร้างบ้านเดี่ยว 2 ชั้น ด้วยชิ้นส่วนสำเร็จรูปเสา-คาน กับการก่อสร้างระบบเดิม - นรินทร์ พุทธอารักษ์วงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The main purpose of this study was to make a comparison between the construction method using prefabricated columns and beams and the conventional construction method. The compared aspects were their construction techniques, problems arising during the construction, obstacles affecting the construction, their advantages and disadvantages, their costs and their construction timeframe. The subjects were two-storey houses with a functional area of 270 square meters in a housing estate project where these two methods were used. The data was collected through observation, recording, interviews and taking photographs of each stage of construction from the beginning to the end. It was found that the cost for constructing house frames using prefabricated columns and beams increased by 4.00%, accounting for 77,956 baht.In terms of sanitation, the cost decreased by 1.27%, accounting for 24,628 baht, However, the costs for other construction jobs stayed the same. The construction cost for a combination of the two methods was 10,493.39 baht a a square meter. The cost of this was higher than that of the conventional method by 0.89%, accounting for 25,167.79 baht. When the average costs per square meter of the two methods were compared, it was found that the cost of the combined method was 10,568.60 baht a square meter while the cost of the conventional method was 10,493.39 baht a square meter. The cost of the first method was 93.21 baht higher than that of the second method. As for the timeframe for completion, the conventional method took 178 days while the combination method took 152 day. The timeframe of the combination method was 26 days shorter than that of the conventional method.It can be concluded that to construct a two-storey house for a real estate project, the construction method using prefabricated columns and beams is ideal because of the shorter construction timeframe. It is worth mentioning that if this method is used, the quality of the prefabricated parts and the installation of the parts have to be strictly controlled because the installation of the parts in the houses in this study was substandard.